Experimental and finite element analysis on flexural behavior of mortar beams with chemically modified kenaf fibers. (19th July 2021) - Guo, Aofei; Sun, Zhihui; Satyavolu, Jagannadh
Highlights: Kenaf fibers are chemically modified. Effect of modified kenaf fibers on flexural behavior of mortars was investigated. Effect of fiber dosage on flexural behavior of mortars was examined. Effect of fiber type on flexural behavior of mortars was discussed. Finite element analysis was conducted to model flexural behavior of mortars. Abstract: In this study, raw kenaf fibers (RKF), alkaline treated kenaf fibers (AKF), and alkaline-hydrogen peroxide treated kenaf fibers (AHPKF) were prepared and then incorporated into mortar to evaluate their impact on the flexural behavior of mortar. In addition to the fiber type, the effect of fiber dosage (0.25%, 0.5%, and 0.75% by weight of cement) on flexural behavior was also studied. Finite element analysis (FEA) was conducted to assist in examining the stress and cracking strain within the mortar specimens. The results show that with the increase of fiber dosage, although the compressive strength and flexural strength of the mortar decrease, a huge improvement of flexural toughness can be achieved. By comparing these three types of kenaf fibers, AKF provides the best performance compared to the other two. With the addition of superplasticizer, the flexural behavior of mortar can be further improved. The microstructure analysis provides some insight into the flexural behavior of mortars with chemically modified kenaf fibers. Lastly, the finite element analysis indicates that the presence of fibers in mortar can increase the residual load, slow down crack propagation, and reduce the cracking strain.